If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(2n+2)=6(8n+3)+3
We simplify the equation to the form, which is simple to understand
2(2n+2)=6(8n+3)+3
Reorder the terms in parentheses
+(+4n+4)=6*(8n+3)+3
Remove unnecessary parentheses
+4n+4=+6+*(+8n+3+)+3
Reorder the terms in parentheses
+4n+4=+(+48n+18)+3
Remove unnecessary parentheses
+4n+4=+48n+18+3
We move all terms containing n to the left and all other terms to the right.
+4n-48n=+18+3-4
We simplify left and right side of the equation.
-44n=+17
We divide both sides of the equation by -44 to get n.
n=-0.386363636364
| 48=5/8f+23 | | -4k=42.4 | | 0.7x-4.1=0.1 | | 9(x-3)/6=3(x+8)/13 | | -x/5+5=15 | | 2y^3+5y^2-3y=0 | | 1x+.15x=52.19 | | m^2-16m=8 | | 1.5=4x-8.5 | | z-7=8 | | 4x+2=4(x-2) | | 2x-2+8x=5 | | lnx^2=0 | | 11.4+10.2*10.9-7.3= | | x//5-=x/5 | | z-12=-9 | | -5(5x-1)+5=-25x+10 | | 4y+10=30 | | log(4a-112)=3 | | x^5-4x^3-x^2+5x+2=0 | | 2x-15x-53=0 | | 8x+x^2=11 | | u(u)+5u+4=0 | | a^2-13a+10=0 | | 20-16t^2+32t=0 | | 3[6x-2(y-3)]= | | (3X+5)+(2X-1)=(X-2)-(3X-4) | | x^3-6x^2+9x+2=x^2-7x+14 | | 2(7x+1)=14x+2 | | 5m^2-2m=m+3m^2 | | 3(5y+5)-4(y-3)= | | 0.3f=2.173 |